High-Resolution Mass Spectrometry for Characterizing the Metabolism of Synthetic Cannabinoid THJ-018 and Its 5-Fluoro Analog THJ-2201 after Incubation in Human Hepatocytes. (6th January 2020) - Diao, Xingxing; Wohlfarth, Ariane; Pang, Shaokun; Scheidweiler, Karl B; Huestis, Marilyn A
Abstract: BACKGROUND: Despite increasing prevalence of novel psychoactive substances, no human metabolism data are currently available, complicating laboratory documentation of intake in urine samples and assessment of the drugs' pharmacodynamic, pharmacokinetic, and toxicological properties. In 2014, THJ-018 and THJ-2201, synthetic cannabinoid indazole analogs of JWH-018 and AM-2201, were identified, with the National Forensic Laboratory Information System containing 220 THJ-2201 reports. Because of numerous adverse events, the Drug Enforcement Administration listed THJ-2201 as Schedule I in January 2015. METHODS: We used high-resolution mass spectrometry (HR-MS) (TripleTOF 5600 + ) to identify optimal metabolite markers after incubating 10 μmol/L THJ-018 and THJ-2201 in human hepatocytes for 3 h. Data were acquired via full scan and information-dependent acquisition triggered product ion scans with mass defect filter. In silico metabolite predictions were performed with MetaSite and compared with metabolites identified in human hepatocytes. RESULTS: Thirteen THJ-018 metabolites were detected, with the major metabolic pathways being hydroxylation on the N -pentyl chain and further oxidation or glucuronidation. For THJ-2201, 27 metabolites were observed, predominantly oxidative defluorination plus subsequent carboxylation or glucuronidation, and glucuronidation of hydroxylated metabolites. Dihydrodiol formation on the naphthalene moiety was observed for both compounds. MetaSite prediction matched well with THJ-018 hepatocyte metabolites but underestimated THJ-2201 oxidative defluorination. CONCLUSIONS: With HR-MS for data acquisition and processing, we characterized THJ-018 and THJ-2201 metabolism in human hepatocytes and suggest appropriate markers for laboratories to identify THJ-018 and THJ-2201 intake and link observed adverse events to these new synthetic cannabinoids.